Legal Regulation of Interaction of Security Service of Ukraine with Civil Society in Counteracting Terrorism - A. Yu. Helzhynskyi (Law and Safety)
The relevance of the research is determined by the prerequisites for the rise in the levels of terrorist threats in Ukraine and the development of international terrorism. In response to these threats, the state creates protective mechanisms, increasing the level of protection of the population, since this is one of its main tasks. However, this system does not fully meet its objectives without cooperation with civil society. That is why, one of the current tasks is to unite the efforts of the state and civil society institutions in fighting against terrorism.